Performance enhancement of a Lorentz force velocimeter using a buoyancy-compensated magnet system. (5th June 2015) - Ebert, R; Leineweber, J; Resagk, C
Abstract: Lorentz force velocimetry (LFV) is a highly feasible method for measuring flow rate in a pipe or a duct. This method has been established for liquid metal flows but also for electrolytes such as saltwater. A decrease in electrical conductivity of the medium causes a decrease of the Lorentz force which needs to be resolved, affecting the accuracy of the measurement. We use an electrical force compensation (EFC) balance for the determination of the tiny force signals in a test channel filled with electrolyte solution. It is used in a 90°-rotated orientation with a magnet system hanging vertically on its load bar. The thin coupling elements of its parallel guiding system limit the mass of the magnets to 1 kg. To overcome this restriction, which limits the magnetic flux density and hence the Lorentz forces, a weight force compensation mechanism is developed. Therefore, different methods such as air bearing are conceivable, but for the elimination of additional horizontal force components which would disturb the force signal, only compensation by lift force provided by buoyancy is reasonable. We present a swimming body setup that will allow larger magnet systems than before, because a large amount of the weight force will be compensated by this lift force. Thus the implementation of this concept has to be made with respect to hydrodynamical and mechanical stability. This is necessary to avoid overturning of the swimming body setup and to prevent inelastic deformation. Additionally, the issue will be presented and discussed whether thermal convection around the lifting body diminishes the signal-to-noise ratio (SNR) significantly or not.